2020
DOI: 10.1093/tas/txaa108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of monensin inclusion and level of intake in limit-feeding strategies for beef cows1

Abstract: ABSTRACT A study was conducted to evaluate effects of intake management and ionophore inclusion on diet utilization under managed intake conditions in beef cattle. Two experiments utilized common diets fed at 120% (H) or 80% (L) of maintenance with either 0 or 200 mg/d monensin in a factorial arrangement. Forty cows were fed for 56 d (Exp. 1) to evaluate effects on diet utilization and energy retention; diets were fed to16 ruminally cannulated steers (Exp. 2) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 24 publications
1
8
3
Order By: Relevance
“…Differences were not observed between treatments for GE digestibility, and DE and ME were calculated from digestibility of GE. When this diet was fed at the same level of restriction, Trubenbach et al (2019) and Boardman et al (2020) observed OM digestion (71.7% and 76.7%, respectively) and GE (68.6% and 75.2%, respectively) compared to those in the present study. In our experiment, energy availability was not altered by the time concentrate was delivered (2.54 Mcal ME/kg DM), but was approximately 10% greater than observed in the prior studies ( Trubenbach et al, 2019 ; Boardman et al, 2020 ; 2.18 and 2.38 Mcal ME/kg DM, respectively).…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Differences were not observed between treatments for GE digestibility, and DE and ME were calculated from digestibility of GE. When this diet was fed at the same level of restriction, Trubenbach et al (2019) and Boardman et al (2020) observed OM digestion (71.7% and 76.7%, respectively) and GE (68.6% and 75.2%, respectively) compared to those in the present study. In our experiment, energy availability was not altered by the time concentrate was delivered (2.54 Mcal ME/kg DM), but was approximately 10% greater than observed in the prior studies ( Trubenbach et al, 2019 ; Boardman et al, 2020 ; 2.18 and 2.38 Mcal ME/kg DM, respectively).…”
Section: Discussioncontrasting
confidence: 48%
“…Each of the four, 20-d experimental periods in the Latin Square comprised 11 d adaptation to treatments ( Trubenbach et al, 2019 ; Boardman et al, 2020 ), 7 d for intake and digestion measurements, 1 d for ruminal fermentation profile measurement, and 1 d for rumen fill and solid passage measurement. Intake and digestion observations were made on d 12 through 18.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant recipients were assigned to receive either 100% (control; n = 9) or 70% (restricted; n = 9) of their total energy requirements according to standard beef cattle nutritional models [ 3 ] from GD 158 through parturition ( Table 1 ). The restriction to 70% of NRC predicted requirements was chosen based on observations that restriction to 80% during mid to late gestation had minimal effect on maternal energy retention due to apparent adaptation in maintenance demand [ 1 , 2 ]. Requirements were estimated per individual based on body weight, and each individual was provided a prescribed daily ration to achieve treatment levels of energy intake (1.54 Mcal/kg NEm = 100%).…”
Section: Methodsmentioning
confidence: 99%
“…Worldwide demand for protein continues to grow as land and other resources become increasingly scarce. These accelerating trends have turned producers’ attention to implementing confinement, or semi-confinement feeding in an attempt to increase production per unit area of land, and improve animal nutrient utilization by reducing feed intake [ 1 , 2 ]. Semi-confinement feeding allows for a high degree of control over nutritional management and affords producers the potential opportunity to significantly improve the efficiency of nutrient utilization in beef cows.…”
Section: Introductionmentioning
confidence: 99%